Zemenfes Tsighe, Saleh Mahmud Idris, Yonas Mesfun Asfaha, Senai Woldeab Andemariam, Rediet Kifle Taddese, Ghebrebrhan Ogubazghi, eds, International Conference on Eritrean Studies, 20–22 July 2016: Proceedings - Nosnitsin, Denis (Aethiopica, 2022)
Review